Tetrahedral DNA Framework-Programmed Electrochemical Biosenors with Gold Nanoparticles for Ultrasensitive Cell-Free DNA Detection - Chenguang Wang; Wei Wang; Yi Xu; Xiaoshuang Zhao; Shuainan Li; Qiuling Qian; Xianqiang Mi (Nanomaterials, 2022)
Tumor-associated cell-free DNA (cfDNA) is a dynamic biomarker for genetic analysis, early diagnosis and clinical treatment of cancers. However, its detection has limitations because of its low abundance in blood or other complex bodily fluids. Herein, we developed an ultrasensitive cfDNA electrochemical biosensor (E-cfDNA sensor) based on tetrahedral DNA framework (TDF)-modified gold nanoparticles (Au NPs) with an interface for cfDNA detection. By accurately controlling the numbers of base pairs on each DNA framework, three types of TDFs were programmed: 26 base pairs of TDF; 17 base pairs of TDF; and 7 base pairs of TDF (TDF-26, TDF-16 and TDF-7, respectively). We also combined the TDF with hybridization chain reaction (HCR) to achieve signal amplification. Under optimal conditions, we detected the breast cancer susceptibility gene 1 (BRCA-1), a representative cfDNA closely related to breast cancer. An ultra-low detection limit of 1 aM with a linear range from 1 aM to 1 pM by TDF-26 was obtained, which was superior to the existing methods. Each type of TDF has excellent discrimination ability, which can distinguish single mismatch. More significantly, we also detected BRCA-1 in mimic serum samples, demonstrating that the E-cfDNA sensor has potential use in clinical research.